Renewing polyethylene: insertion copolymerization of sugar derived hydrophilic monomers with ethylene - Rajput, Bhausaheb S.; Pawal, Sandip B.; Bodkhe, V. Dnyaneshwar; Rao, I. Nagamalleswara; Sainath, Annadanam V. Sesha; Chikkali, Samir H. (European Polymer Journal, 2020)
Although highly desirable, insertion copolymerization of renewable resource derived functional olefins with ethylene has been rarely investigated. Herein, we report insertion copolymerization of challenging sugar derived isohexide mono-enes with ethylene in the presence of Pd-phosphinesulfonate acetonitrile catalyst (C1). Thus, copolymerization of ethylene with isomannide mono-ene (2a), isosorbide mono-ene (2b'), isoidide mono-ene (2c) and methacryl-2,3,4,6-tetra-O-acetyl-D glucopyranoside (2d) afforded corresponding functionalized polyethylene (P2a-1 to P2d-1). High temperature proton NMR investigations revealed enchainment of 2a-2c in polyethylene backbone and the highest incorporation of 1.45% was observed for 2c. The high temperature proton NMR results were further corroborated by solid state C-13 NMR and IR spectroscopy. Gel permeation chromatography analysis displayed weight average molecular weight in the range of 13.0-27.2 x 10(3) g/mol. The thus prepared copolymers revealed melting temperature in the range of 117-126 degrees C. Relatively reduced melting temperature compared to neat polyethylene may suggest an irregular arrangement of pendant functional group on polyethylene main chain.
Keywords: Hydrophilic polyethylene; insertion copolymerization; Isohexide mono-enes; Polyethylene; Sugar

Refining plant oils and sugars to platform chemicals, monomers, and polymers - Pandey, Swechchha; Rajput, Bhausaheb S.; Chikkali, Samir H. (Green Chemistry, 2021)
As fossil resources continue to dwindle and environmental concerns are magnified, finding sustainable alternatives is the only way to mitigate resource availability and derisk the planet. The principles of Green Chemistry may provide guidance in this case, and renewable resources can be converted into useful platform chemicals, monomers, and polymers. This critical review examines the possibility of utilizing renewable plant oils and sugars to produce feedstock chemicals, monomers, and polymers. Among the seven isomerizing functionalization reactions of plant oils, isomerizing alkoxycarbonylation displays the highest terminal selectivity. Despite the low reactivity of sugar-derived isohexides, new strategies have been deployed to convert isohexides into difunctional monomers and polymers. The commercialization of isohexides and a few polymers derived from these building blocks has just commenced. Thus, challenges associated with isomerizing functionalization of plant oils and the use of sugar-derived isohexides in chemical syntheses have been summarized, and the potential of these renewable resources has been evaluated.